Polystyrene nanoparticles induce DNA damage and apoptosis in HeLa cells - Antonia Feola; Manoj Madheswaran; Grazia Romano; Awet Ghebretinsae Tewelde; Eunice Wairimu Maina; Gianluca D'Abrosca; Maria della Valle; Mariacristina Cocca; Maria Emanuela Errico; Carla Isernia; Roberto Fattorusso; MariaTeresa Gentile; et al. (Heliyon)
Nanoplastics (NPs) are plastic particles, typically less than 100 nm in size, that result from daily life products as well as the degradation of larger plastic debris. Due to their small size and chemical composition, they can interact with biological systems in ways that larger plastic particles cannot. Humans are continuously exposed to NPs and several studies showed the potentially toxic effects of these latter on health. Polystyrene nanoplastics (PS-NPs) are the prevalent form of nanoparticles found in the environment and their cellular uptake can cause cytotoxicity and structural alteration of biomolecules. Thus, there is an urgent need for evaluation of the genotoxic effects of PS-NPs on human cell models. Through different and complementary experimental approaches, we investigated the potential genotoxic and cytotoxic effects of PS-NPs exposure on HeLa cell lines. We highlighted the genotoxic effects of polystyrene nanoplastics by showing the formation of multinuclei and micronuclei in all the studied concentrations and time points, also at short incubation time (6 h) and low concentration. At higher concentrations, we demonstrate the presence of apoptotic and necrotic cells outlining the acute cytotoxic effects of nanoplastics. The genotoxic potential is further highlighted by the presence of low molecular weight DNA fragments in PS-NPs treated cells, and by the relationship between polystyrene nanoplastics and γ-H2AX. Thus, our data provide important insights at a cellular level into the possible risks produced by these nanoparticles and recommend further deeper research studies to address the impacts of nanoplastics on human health.